Special issue dedicated to the memory of Ivan Šetlík - Prášil, Ondřej (Folia microbiologica, 2019)
The following series of articles form a special issue organized by the Algatech Center of the Institute of Microbiology CAS dedicated to the memory of Dr. Ivan Šetlík.
Keywords: Photosynthesis; History, 21st Century; Czechoslovakia; biopaliva; dějiny 20. století; Microbiology; mikrobiologie; Cyanobacteria; History, 20th Century; fotosyntéza; Biofuels; dějiny 21. století; sinice; Československo